Coastal medicinal plant diversity and its role in community health resilience in East Aceh, Indonesia - NURSAMSU NURSAMSU; NURHAFIDHAH NURHAFIDHAH; PANDU PRABOWO WARSODIREJO; MARDUDI MARDUDI (Society for Indonesian Biodiversity, 2025)
Abstract. Nursamsu, Nurhafidhah, Warsodirejo PP, Mardudi. 2025. Coastal medicinal plant diversity and its role in community health resilience in East Aceh, Indonesia. Biodiversitas 26: 6335-6351. The coastal medicinal plant diversity represents an important component of community health resilience. This study documented the diversity and use patterns of medicinal plants utilized by coastal communities in East Aceh, Indonesia. Semi-structured interviews and field walks were conducted in five villages Kuala Idi, Gampong Aceh, Blang Geulumpang, Ulee Blang, and Titi Baro covering 100 informants. A total of 125 taxa from 55 families were identified, dominated by the Poaceae family. The highest Use Value (UV) was recorded for Cocos nucifera (0.92) , while the maximum Relative Frequency of Citation (RFC) reached 0.98 for Oryza sativa, Piper betle, and Alpinia galanga. Sixteen disease categories were classified based on WHO ICD-10, totaling 11,456 use reports, with Informant Consensus Factor (ICF) values between 0.98-1.00, indicating strong community agreement. Leaves were the most frequently used plant part (42.4%), and drinking (60.8%) was the predominant method of administration. Diversity indices were high across all sites (Simpson 1-D = 0.9918-0.9920; Shannon H′ = 4.813-4.823), reflecting balanced species distribution and rich ethnobotanical knowledge. These findings highlight the pivotal role of coastal biodiversity in sustaining traditional medicine systems and community health. Strengthening conservation, sustainable utilization, and knowledge transmission is vital to preserving these resources for future generations.